Contemporary Danish politicians : 45 portraits with a brief look at the development of Danish parliamentary democracy - Hansen, Poul (Copenhagen : Det danske Selskab, 1949)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Denemarken